Effects of a bioadhesive barrier-forming oral liquid on pain due to radiation-induced oral mucositis in patients with head and neck cancer: A randomized crossover, preliminary study - Soutome, Sakiko (J Dent Sci, 2021)
BACKGROUND/PURPOSE: Bioadhesive barrier-forming oral liquid, is a recently developed medical material for the management of pain caused by oral mucositis associated with cancer radiotherapy or chemotherapy. The purpose of this study was to evaluate the effectiveness of this liquid in relieving pain resulting from radiation-induced oral mucositis in patients with head and neck cancer. MATERIALS AND METHODS: This randomized, crossover trial investigated the analgesic effects of bioadhesive barrier-forming oral liquid using dexamethasone ointment as a control. Fifteen patients with mild or moderate pain due to radiation-induced oral mucositis were randomly assigned to two groups. Group A applied dexamethasone ointment once on day 1, had a wash-out period on day 2, and used bioadhesive barrier-forming oral liquid once on day 3. Conversely, group B used bioadhesive barrier-forming oral liquid on day 1, had a wash-out period on day 2, and applied dexamethasone ointment once on day 3. The effectiveness in relieving pain was compared between the two groups. RESULTS: One patient reported nausea immediately after the application of bioadhesive barrier-forming oral liquid and was therefore excluded from the analysis. Dexamethasone ointment and bioadhesive barrier-forming oral liquid relieved pain in 85.7% and 71.4% patients, respectively (p = 0.682). Nine patients wished to continue dexamethasone ointment after the study, while only five wished to continue bioadhesive barrier-forming oral liquid. CONCLUSION: Our findings suggest that the analgesic effect of bioadhesive barrier-forming oral liquid is comparable or inferior to that of dexamethasone ointment in patients with radiation-induced oral mucositis. Further studies are needed to verify these findings.